1990
DOI: 10.2224/sbp.1990.18.1.169
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Facial Hair on Impression Formation

Abstract: The influence of facial hair on the perception of a job applicant by persons in business was examined in this study. Subjects were 228 persons in management positions who made hiring decisions. Subjects were shown ink sketches of six male job applicants. The sketches varied on three facial hair dimensions-clean shaven, moustached, and bearded. Sketches were evaluated on semantic differential scales. Results indicated consistently more positive perceptions of social/physical attractiveness, personality, compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 13 publications
1
31
0
2
Order By: Relevance
“…In order to modify one specific feature of a face on a photo while leaving the other features intact, researchers have retouched photos [CARELLO et al 1989] and computer images [LAENG et al 2007], drawn stubble on models [MUSCARELLA and CUNNINGHAM 1996], or used drawings of faces with definite features in place of photos MCARTHUR 1986, REED andBLUNK 1990]. Judges have been allowed to portray their conception of the most attractive face by using sticks to form the face [HERSHON and GIDDON 1980], moving disks to denote eyes and lips [FRĄC-KIEWICZ 2001], or even employing a system of hinged telescopic pipes [SERGL et al 1998].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to modify one specific feature of a face on a photo while leaving the other features intact, researchers have retouched photos [CARELLO et al 1989] and computer images [LAENG et al 2007], drawn stubble on models [MUSCARELLA and CUNNINGHAM 1996], or used drawings of faces with definite features in place of photos MCARTHUR 1986, REED andBLUNK 1990]. Judges have been allowed to portray their conception of the most attractive face by using sticks to form the face [HERSHON and GIDDON 1980], moving disks to denote eyes and lips [FRĄC-KIEWICZ 2001], or even employing a system of hinged telescopic pipes [SERGL et al 1998].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies found a positive correlation [PELLEGRINI 1973, PAN-CER and MEINDL 1978, HATFIELD 1986, REED and BLUNK 1990, HELLSTRÖM and TEKLE 1994 while others found a negative correlation [FEINMAN and GILL 1977, CUNNINGHAM et al 1990, WO-GALTER and HOSIE 1991, MUSCARELLA and CUNNINGHAM 1996. Nevertheless, there is general agreement that men with beards are perceived as older, more mature, manly, dominant, aggressive and threatening [CUNNINGHAM et al 1990, REED and BLUNK 1990, WOGALTER and HOSIE 1991, BARBER 1995, MUSCA-RELLA and CUNNINGHAM 1996. Because a beard accentuates the lower part of the face, men with beards are perceived as more masculine, just as are men with large jaws and chins.…”
Section: Other Determinants Of Facial Attractivenessmentioning
confidence: 99%
“…Wearing a beard tends to increase judgments of qualities usually attributed to men, such as masculinity, aggressiveness, dominance, strength, and self-confidence (Addison, 1989;Kenny and Fletcher, 1973;Pancer and Meindl, 1978;Pellegrini, 1973;Reed and Blunk, 1990;Roll and Verinis, 1971). In a study by Wood (1986), putting on a false beard and taking a look in the mmor increased self-perceived masculinity Freedman (1969) hypothesized that beardedness was adaptive in human evolution, and suggested that 'beards make men more appealing to women and perhaps help love to blossom.…”
Section: General Introductionmentioning
confidence: 99%
“…Likewise, female preferences for facial hair, a sexually dimorphic trait, are highly variable (B. J. W. Dixson & Brooks, 2013; B. J. W. ; B. J. W. Dixson & Vasey, 2012;Feinman & Gill, 1977;Janif, Brooks, & Dixson, 2014;Muscarella & Cunningham, 1996;Pellegrini, 1973;Reed & Blunk, 1990;Wogalter & Hosie, 1991).…”
Section: The Darwinian Paradox Of Individual Differencesmentioning
confidence: 99%
“…Likewise, beardedness enhances men's attractiveness to women in some studies (B. J. W. Janif et al, 2014;Pellegrini, 1973;Reed & Blunk, 1990) but not in others (B. J. W. Dixson, Tam, & Awasthy, 2013; B. J. W. Dixson & Vasey, 2012;Feinman & Gill, 1977;Muscarella & Cunningham, 1996;Wogalter & Hosie, 1991), while in other cases preferences between clean-shaven faces and those with full beards are more equivocal (B. J. W. Dixson & Brooks, 2013;Neave & Shields, 2008;Saxton, Mackey, McCarty, & Neave, 2016). Even within traits for which women typically state strong preferences, such as deeper vocal pitch and muscularity (B. J. W. Dixson, Grimshaw, Ormsby, & Dixson, 2014;Frederick & Haselton, 2007), effect sizes for ratings of dominance tend to be greater than those for attractiveness (Puts, 2010).…”
Section: Introductionmentioning
confidence: 95%